Hardware Security Module Cryptosystem Using Petri Net - Billel Guechi; Mohammed Redjimi (IAES Indonesian Section, 2023)
An embedded system is a combination of hardware and software designed to perform specific functions. It consists of SoCs (system on chip) that it relies on to do its computing work. A key feature of an embedded system is that it consumes less power and components occupy less space on the IC (integrated circuit) thus, the use of SoCs. Embedded system manufacturers get these SoCs from third-party companies to reduce their time to market. That would increase the possibility of the systems to be compromised. In this paper, we present a novel approach to securing such critical systems. For that, we made a Hardware Security Module (HSM), which consists of secure SoC with encrypt/decrypt engine that use Petri net for algorithm modulation to secure data flow. We ensure that the system uses genuine firmware and data is secured since we use encrypt/decrypt algorithms only known to manufacturers.